"Vocational education and training is a crucial lever for successfully coping with transformation processes" : an interview with Dr. JÜRGEN SIEBEL on the challenges facing vocational education and training in Europe - Siebel, Jürgen [Interviewter] (My University, 2020)
"In 2020, vocational education and training (VET) in Europe will need to take stock and make new plans. Many strategy papers and initiatives are oriented towards this year. The new European Commission’s work programme for the next five years has been available since January. New perspectives will open up for VET as a result of this plan and in the wake of Brexit. The European Centre for the Development of Vocational Training (Cedefop) has acted as a reference centre for the EU since its establishment in 1975. It observes the development of VET systems and supports representatives from the fields of policy, practice and research in the further development of VET in Europe. In this interview, Cedefop’s Executive Director Dr. JÜRGEN SIEBEL outlines his assessment of current and future challenges and provides insights into the work carried out by the centre." (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; S 3.5.5.1 CEDEFOP; Berufsbildung; EU-Bildungspolitik; CEDEFOP